Subcycle Controlled Charge-Directed Reactivity with Few-Cycle Midinfrared Pulses - Znakovskaya, I.; von den Hoff, P.; Marcus, G.; Zherebtsov, S.; Bergues, B.; Gu, X.; Deng, Y.; Vrakking, M. J. J.; Kienberger, R.; Krausz, F.; de Vivie-Riedle, R.; Kling, M. F. (My University, 2012)
The steering of electron motion in molecules is accessible with waveform-controlled few-cycle laser light and may control the outcome of light-induced chemical reactions. An optical cycle of light, however, is much shorter than the duration of the fastest dissociation reactions, severely limiting the degree of control that can be achieved. To overcome this limitation, we extended the control metrology to the midinfrared studying the prototypical dissociative ionization of D2 at 2.1 μm. Pronounced subcycle control of the directional D+ ion emission from the fragmentation of D+2 is observed, demonstrating unprecedented charge-directed reactivity. Two reaction pathways, showing directional ion emission, could be observed and controlled simultaneously for the first time. Quantum-dynamical calculations elucidate the dissociation channels, their observed phase relation, and the control mechanisms.